Are Mind-Body Exercise Beneficial for Treating Pain, Function, and Quality of Life in Middle-Aged and Old People With Chronic Pain? A Systematic Review and Meta-Analysis - Wen, Yu-Rong; Shi, Jian; Wang, Ya-Fei; Lin, Yang-Yang; Hu, Zheng-Yu; Lin, You-Tian; Wang, Xue-Qiang; Wang, Yu-Ling (Frontiers in Aging Neuroscience, 2022)
Background: Ageing is a significant risk factor in chronic pain development with extensive disability and greater health care costs. Mind-body exercises (MBEs) have been scientifically proven to affect pain intensity and physical health. Objectives: To assess the effects of MBE modes (Tai Chi, Yoga, and Qigong) for treating chronic pain among middle-aged and old people, compared to non-active and active treatment, as well as function, quality of life, and adverse events. Methods: We searched PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Database, and Chinese Scientific Journals Full-Text Database (VIP) to March 2022. No restrictions were chartered within the year and language of publication. We included randomized controlled trials of MBE treatment in middle-aged and elderly people with chronic pain. The overall certainty of evidence was evaluated by using the GRADE approach. Results: A total of 17 studies (n = 1332) were included in this review. There was low-certainty evidence indicated that MBEs had a moderate effect on reducing pain compared with the non-active and active control group (SMD -0.64, 95% CI -0.86 to -0.42, P＜0.001). Very-low-certainty evidence showed the pooled SMD for the functional improvement was -0.75 (95% CI -1.13 to -0.37, P < 0.001). Low-certainty evidence presented that no influence was observed in physical component summary (SMD 0.23, 95% CI -0.16 to 0.62, P = 0.24) and mental component summary (SMD -0.01, 95% CI -0.39 to 0.36, P = 0.95). Conclusion: Our results indicated that MBEs were effective treatments for reducing symptoms of middle-aged and elderly people with chronic pain compared with non-active and active control groups. TC and Qigong had obvious benefits for knee osteoarthritis in self-reported function, but the efficacy of chronic low back pain was uncertain. No significant benefit of MBE on quality of life in older adults with chronic pain was found. More high-quality RCTs should be conducted to explore the efficacy and mechanism of MBEs on chronic pain in middle-aged and elderly people from various dimensions, such as affective and cognitive dimensions.